4.3k views
1 vote
Can you please show work

Can you please show work-example-1
User Vegidio
by
5.3k points

1 Answer

3 votes

The expression B.
(1)/(9^(16) ) is equivalent to
(9^(-2)) ^(8) .

Explanation:

Step 1:

For the given number, -2 and 8 are both exponents.

According to the power rule,
(a^(x)) ^(y) = a^(xy).

Here a is 9, x is -2 and y is 8.

Substituting the values, we get
(9^(-2)) ^(8) = 9^((-2)(8)) .


9^((-2)(8)) = 9^(-16) .

Step 2:

According to the negative exponent rule, we have
a^(-z) = (1)/(a^(z) ) .

Here a is 9 whereas z is equal to 16.

So
9^(-16) = (1)/(9^(16) ) .

This is represented by option B.

User AndOs
by
6.4k points